Sucesión secundaria en un abedular-hayedo en el Parque Natural de Urquiola (Vizcaya) - Herrera, Javier; Laskurain, Nere Amaia; Loidi, Javier; Escudero, Adrián; Olano, José Miguel (Lazaroa, 2001)
By means of tree-ring analysis of beeches (Fagus sylvatica) and birches (Betula celtiberica) the history of a young forest in the Natural Park of Urquiola (Vizcaya) has been reconstructed. The original forest was cut down in the mid-forties to establish a Pinus radiata plantation. The plantation was rather heterogeneus, with many birches and beeches subsequently becoming established, which were at least partly spared when the pine forest was felled in 1967. A huge number of birch established themselves just after the felling, and it is now the most abundant species. Beech trees established themselves continuously over time, whereas birch establishment was concentrated in the periods following disturbance. Our results corroborate a dynamic model for these ecosystems, with birch as the pioneer species and beech becoming dominant later.